Serum neutrophil gelatinase-associated lipocalin and oxidized neutrophil proteins in patients with nephropathy caused by acute alcohol poisoning - Lyudmila Andreevna Demidchik; Dmitriy Anatolyevich Klyuyev; Larissa Yevgenievna Muravlyova; Vilen Borisovich Molotov-Luchanskiy; Ryszhan Yemelevna Bakirova; Olga Anatolyevna Ponamareva; Yevgeniya Alexandrovna Kolesnikova; Dina Daniyarovna Baymagambetova; Ahmet Kiziltunc (Society of Diabetic Nephropathy Prevention, 2021)
Introduction: Alcohol use has been identified as a major risk factor for disease burden and premature mortality. Objectives: We studied the serum neutrophil gelatinase-associated lipocalin (NGAL) and advanced oxidation protein product (AOPP) concentrations in neutrophils to assess the possibility of their using for the early detection of kidney damage in patients with acute alcohol poisoning (AAP). The impact of eGFR (estimated glomerular filtration rate) on the NGAL and AOPP levels was also studied. Patients and Methods: The study included 89 patients with AAP. Healthy individuals and patients with chronic kidney disease (CKD) served as comparison groups. Participants were represented by men, aged between 20 and 40 years. Results of laboratory tests of kidney function were also taken into account. Serum NGAL level was measured using ELISA kit. AOPP was determined using the method of Witko-Sarsat et al. Results: We detected a significant increase in serum NGAL and AOPP level both in toxic nephropathy with a clinical picture of acute kidney injury (AKI) and in the "preclinical stage" of kidney damage. Hence a single trend in the changes of these indicators existed in patients with AAP. At the same time, our study revealed opposite trends in patients with CKD. There was no significant increase in serum NGAL in patients with CKD. Conclusion: We propose to consider an increased eGFR together with an increased serum NGAL concentration in patients with AAP as the stage, preceding the nephropathy or AKI, even in the absence of clinical and laboratory signs of impaired renal function.